Location on RP4 of a tellurite resistance determinant not normally expressed in IncP alpha plasmids. - Taylor, D E (1987)
The tellurite resistance (Ter) determinant of RP4 is not normally expressed unless variants are selected on medium containing tellurite. The determinant was mapped in the variant plasmid RP4Ter by Tn7 insertion mutagenesis. Based on a 56.4-kilobase (kb) replicon, it covered the region from 56 kb, across the EcoRI site at 0 kb, to 1.5 kb.